Laulības tiesiskās izpratnes veidošanās un attīstība Latvijā - Švarca, Dzintra (Latvijas Universitāte, 2006)
Pētījums “Laulības tiesību izpratnes attīstība Latvijā” ir veltīts laulības institūta un tam piederīgo elementu – saderināšanās, laulības šķēršļu un laulības noslēgšanas ģenēzes un evolūcijas problemātikai. Maģistrante aizstāvībai ir izvirzījusi šādus secinājumus un priekšlikumus. Atbilstoši Civillikumā nostiprinātajām tiesībām, ar saderināšanos reglamentējošām normām ir risinātas saderināto mantiskās attiecības, ja paredzētā laulība nav notikusi. Galvenā apsolījuma izpilde – laulības noslēgšana ir tikumiskas dabas jautājums un normatīvu regulējumu neprasa. Tāpēc tās regulējums Civillikumā ir lieks. Civillikums satur novecojušos noteikumus par obligātu izsludināšanu pirms laulības, kas savu funkciju vairs nepilda. Tāpēc izsludināšanu reglamentējošu noteikumu atrašanās Civillikumā nav pamatota.

This research “Development of the judicial comprehension of the Law of Marriage in Latvia” gives attention to the marital institution and belonging elements to it – betrothal, proclamation, impediments to marriage, as well as entering into marriage – genesis and problems of the evolution. The author was proposed some conclusions and suggestions. There are two forms of legally acknowledged marriage in Latvia – civilmarriage and marriage witch is settled in church. Both forms of marriage are approved by the Civil Law and historicaly motivated in Latvia. According to rights set forth in the Civil Law, norms regulating betrothal also regulate property relations of the betrothed in case the marriage has not taken place. Fulfillment of the main promise – entering into marriage – is a moral question and does not require normative regulations. Therefore, it is unnecessary to regulate in the Civil Law the above-mentioned fulfillment of the promise. The Civil Law contains outdated rules concerning mandatory proclamation before marriage which do not function anymore. Therefore, the presence of rules regulating proclamation in the Civil Law is not justified.
Formation and Develpment of Legal Comprehension of Marriage in Latvia
Keywords: Juridiskā zinātne